Somatostatin Receptor Expressing Bilateral Ovarian Metastases Detected by 68Ga DOTANOC PET/CT. (June 2015) - Arora, Saurabh; Soundararajan, Ramya; Joshi, Prashant; Kumar, Rakesh; Bal, Chandrasekhar
Abstract : Abstract: Bilateral ovarian metastasis from neuroendocrine tumor (NET) is uncommon. Ovarian NET could be primary or metastatic, and if it is bilateral, then the chances of metastatic disease are from 88% to 94%. Proper identification and appropriate management become necessary in such patients. Somatostatin receptor imaging by 68 Ga-labeled DOTANOC ([1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid]-1-NaI3-Octreotide) PET/CT can be used for localization, staging, and restaging of NET, and it also has an impact on appropriate clinical management of patients with NET. We present here a case of somatostatin receptor expressing bilateral ovarian metastases from NET demonstrated by 68 Ga DOTANOC PET/CT imaging.